Effectiveness of Green Mussel Chitosan Supplement in Feed on the Growth of Vaname Shrimp (Litopenaeus vannamei) - Fadhilah, Ika Nur; Firmani, Ummul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
White shrimp (Litopenaeus vannamei) is an important aquaculture commodity with production demand that continues to increase every year. The addition of chitosan from green mussel shells in feed can increase calcium availability, support the moulting process, and increase shrimp growth and survival. This study aims to examine the effectiveness of green mussel chitosan supplements on the growth and survival of vaname shrimp. This research consists of three stages, namely making chitosan nanoparticles from green mussel shells, making feed with various doses of chitosan nanoparticles (0%/A, 10%/B, 15%/C, and 20%/D), and cultivating vaname shrimp. Feed is made by mixing chitosan nanoparticles with commercial feed, then drying and crushing it into small crumbs. White vaname shrimp are kept in concrete ponds for 80 days, with water quality monitoring and regular measurements of growth in weight and length. Data shows that C treatment with a dose of 15% chitosan nanoparticles resulted in the highest growth in weight and length of vanamei shrimp, reaching an average weight of 12.58 grams and a length of 14.07 cm on the 80th day. Treatment C provides optimal growth compared to other treatments because chitosan accelerates the moulting process and exoskeleton mineralization. Water quality during the study, including a temperature of 29.99°C, pH 7.23, and ammonia content of 0.25 ppm, was within the tolerable range for shrimp growth.